BUILDING DIGITAL INCLUSION AND NON-DISCRIMINATORY SERVICES IN JAMBI CITY GOVERNMENT FOR VULNERABLE GROUPS - Hapsa; Yusuf, M; Karim, Navarin; Fatriani, Riri Maria (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2024)
This study examines the digital inclusion and non-discriminatory public services provided by the Jambi City Government, with a specific focus on vulnerable groups, including individuals with disabilities, the elderly, and low-income populations. While digital transformation has improved accessibility and efficiency, systemic barriers such as limited digital literacy, inadequate infrastructure, and affordability challenges persist, leading to disparities in service utilization. Through a qualitative analysis using secondary data and Nvivo 12Plus, this research identifies key indicators influencing digital inclusion, including accessibility, digital literacy, privacy, and security, while highlighting affordability and public digital service usage as critical areas for improvement. The findings emphasize the importance of a multidimensional approach involving policy interventions, technological advancements, and community engagement to enhance digital equity. By addressing these challenges, Jambi City can foster a more inclusive digital governance model that ensures equitable access to public services for all citizens.